Braveheart - Gibson, Mel (Diliman, Quezon City : Viva Video, 1999)
Mel Gibson stars and directs this sweeping saga about Scotland's brutal battle for independence in the 13th century. When William Wallace's (Mel Gibson) wife is ravaged and murdered by English troops, his quest for revenge quickly turns into an impassioned fights for his country's freedom.ales of Wallace's bravery inspire every commoner to take arms against the English and escalate their crusade into a full scale war.
Keywords: Wallance, William Sir, d. 1305 -- Drama; Scotland -- History -- Wallace's Rising, 1297-1304 -- Drama